2021
DOI: 10.7831/ras.9.0_178
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Disaster Mitigation Strategies in Indonesia

Abstract: Indonesia experiences various disasters that affect human life in the economic and social aspects. Those disasters also affect the agriculture sector, and farmers have to face destroyed land and crop loss. The lives of farmers become more vulnerable. This paper presents the various disasters in Indonesia that affect agriculture, how the farmers' lives get affected, and how the farmers cope with the impacts of the disasters with various mitigation strategies. Management of disaster risk reduction is being condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 101 publications
(170 reference statements)
0
12
0
2
Order By: Relevance
“…Furthermore, due to historical and cultural connections [45], Javanese culture significantly influences the Banyumas people, including local mitigation practices in the study area. Here, the local farmers apply the indigenous farming technique in the slope area and use the traditional seasonal calendar in Javanese farming [37,38,94]. However, the economic and political transformation has threatened the sustainability of the protected forest in the upper part of the village that preserves water resources for various purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, due to historical and cultural connections [45], Javanese culture significantly influences the Banyumas people, including local mitigation practices in the study area. Here, the local farmers apply the indigenous farming technique in the slope area and use the traditional seasonal calendar in Javanese farming [37,38,94]. However, the economic and political transformation has threatened the sustainability of the protected forest in the upper part of the village that preserves water resources for various purposes.…”
Section: Discussionmentioning
confidence: 99%
“…In Aceh, the smong tradition was essential during significant tsunami events in the Indian Ocean in 1907 and 2004 [30]. In other regions, the Gayo community has developed kekeberen as an oral tradition to preserve local history, moral values, and regulations, including hazard mitigation [16], whereas Javanese people integrate local knowledge to deal with weather patterns (locally called pranata mangsa), especially for agriculture [37,38].…”
Section: Local Mitigation Strategiesmentioning
confidence: 99%
“…and Rural Development Research Moreover, due to the Covid-19 pandemic over the last two years (Djalante et al, 2020;Ing & Basri, 2022;Malahayati et al, 2021;Nugroho et al, 2022;Rozaki et al, 2021) Muhyiddin & Nugroho, 2021;Nugroho et al, 2022;Olivia et al, 2020). The respondents also confirmed that rural infrastructure development appeared to stall in 2020-2022.…”
Section: Policy Implicationmentioning
confidence: 91%
“…Household characteristics include household gross income per capita (Obayelu et al, 2014), arable land per capita (Abid et al, 2015) and other indicators. In addition, crop disaster experience may directly affect farmers' adaptation behavior decisions to climate change (Rozaki et al, 2021). Therefore, "Have crops been damaged by the weather" is included in the model assessment as family experience.…”
Section: Definition Of Variablesmentioning
confidence: 99%